A review of cutting mechanics and modeling techniques for biological materials. (July 2017) - Takabi, Behrouz; Tai, Bruce L.
Highlights: Major works in cutting simulations of soft tissues and bones are reviewed. These simulations focus on cutting forces and chip formation. Fracture is the dominant mechanism in soft tissue cutting. Johnson–Cook model is mostly used for bone cutting finite element simulations. Mesh-free methods have been used for bone cutting but are not yet mature. Abstract: This paper presents a comprehensive survey on the modeling of tissue cutting, including both soft tissue and bone cutting processes. In order to achieve higher accuracy in tissue cutting, as a critical process in surgical operations, the meticulous modeling of such processes is important in particular for surgical tool development and analysis. This review paper is focused on the mechanical concepts and modeling techniques utilized to simulate tissue cutting such as cutting forces and chip morphology. These models are presented in two major categories, namely soft tissue cutting and bone cutting. Fracture toughness is commonly used to describe tissue cutting while Johnson–Cook material model is often adopted for bone cutting in conjunction with finite element analysis (FEA). In each section, the most recent mathematical and computational models are summarized. The differences and similarities among these models, challenges, novel techniques, and recommendations for future work are discussed along with each section. This review is aimed to provide a broad and in-depth vision of the methods suitable for tissue and bone cutting simulations.